La física de los huracanes Paulina y Patricia en su paso por el Pacífico mexicano - Castro Lopez, J.; Zavala Trujillo, B.; Figueroa Lara, A. (Revista Mexicana de Física E, 2020)
One of the most powerful hurricanes that hit the Pacific coast of Mexico has been the Patricia hurricane (category five on the Saffir-Simpson scale of intensity) that occurred in 2015; the hurricane that was a genuine watershed in the mexican culture and the politics of disaster prevention in Mexico was hurricane Pauline (1997). However, even with the above, th dissemenination of knowledge about the physical phenomena that are involved in cyclogenesis and hurricane movement is very scarce, so in this paper we propose to make an introduction to the physics of hurricanes, we address the cyclogenesis theory of a hurricane, one of the most accepted theories about the behavior of its trajectories and important concepts of atmospheric sciences. The main variables that influenced Patricia and Pauline are also discuses, such as: atmospheric pressure, ocean surface temperature, wind direction and speed. Finally, an analysis is made on the formation and trajectory of Pauline and Patricia using the information shown and based on the theory presented (both in a barotropic and baroclinic framework).